Model Persamaan Diferensial Orde Satu Untuk Masalah Kinematika Garis Lurus - Ofirenty E Nubatonis (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2021)
In the history of mathematical modeling, differential equations emerged as a tool to solve various problems in human life, including the development of theories in mathematics. In this research, differential equation models will be constructed for straight line kinematics problems. The method used is the literature review method. The differential equation models obtained are (1) The differential equation with the initial condition is a differential equation model to express the problem of changing the position of the object at time t. The integration of this model will produce an equation for the position of an object, (2) the equation with the initial conditionwhich states the change in velocity at any time t. The integration of this model will produce an equation for the velocity of an object moving in a straight path, (3) The equation to express Newton's Second Law and with the initial condition then the integration will produce a velocity equation that takes into account the mass of the object and the resultant force is given, (4) the equation with the initial condition so that the integration will produce a velocity equation for free falling objects and (5) a first order linear ordinary differential equation and Bernoulli's differential equation to express the change in the velocity of an object in free fall which is affected by air friction.